Prognostic value of the intubation difficulty scale in bariatric surgery - M. O. Maiorov; D. V. Federiakin; E. V. Belevskii; V. N. Silaev; S. I. Tokareva (Вестник анестезиологии и реаниматологии, 2023)
The objective was to assess the predictive value of the risk scale for difficult intubation in obese patients.   Materials and methods. The object of the study was 110 patients (90 women and 20 men) operated on as planned in 2022. The mean age of the patients was 42 ± 11 years. The median body mass index (BMI) was 43.7 kg/m 2 (Q1–Q3: 37.9–49.1). All patients underwent a standard preoperative examination with the identification of the risk of difficult airways according to the intubation difficulty scale (IDS): mouth opening, neck mobility, mandibular protrusion, Mallampati class, sternomental and thyromental distances, and history of previous intubations were assessed.   Results. Difficult intubation (3–4 degrees according to Cormack–Lehane) were detected in 19 patients (17.3 %). ROC-analysis revealed the dependence of the probability of difficult intubation on the total points on the intubation difficulty scale. The area under the ROC curve was 0.809 ± 0.063 with 95 % CI: 0.685 – 0.932. The model was statistically significant (p < 0.001). The cut-off point value for the total points on the intubation difficulty scale, which corresponded to the highest value of the Youden index, was 4. The sensitivity and specificity of the model were 100.0 % and 47.3 %, respectively. Significant differences (p < 0.001) were found in the analysis of the risk of difficult intubation depending on the total points on the intubation difficulty scale. The most significant differences (p < 0.001) were demonstrated by the mouth opening width and neck mobility. There were no differences (p = 0.547) when analyzing the history of difficult airways and nighttime snoring.   Conclusion. Overall, the intubation difficulty scale showed predictive value in terms of assessing the risk of difficult airways (p = 0.002, χ2 = 13.230). The most reliable indicators for predicting the risks of difficult intubation were mouth opening less than 4 cm (p < 0.001, χ2 = 11.185) and head and neck flexion in the atlanto-occipital joint less than 90о (p < 0.001, χ2 = 10.858). Assessment of thyromental and sternomental distances, mandibular protrusion ability, and Mallampati class also showed statistical significance. Prior history of difficult intubation and nighttime snoring showed no statistically significant risk in predicting difficult airways (p = 0.547, χ2 = 0.363).